Pneumococcal Meningitis in an Adolescent with Fever and Foot Ache. (14th July 2013) - Dias, Catarina; Pedrosa, Cláudia; Romariz, Jorge; Santos, Mafalda; Rodrigues, Lúcia
Abstract : Invasive pneumococcal disease predominantly affects younger children, elderly, and immunocompromised patients. Pneumococcal meningitis is a particularly important form of presentation, considering its high rate of morbimortality. We present the case of a previously healthy 12-year-old adolescent male who was hospitalized due to suspicion of osteoarticular infection in his left foot. A few hours later, he developed meningeal signs, exhibiting slight pleocytosis and Streptococcus pneumoniae isolates in both cerebrospinal fluid and blood. Imaging studies were inconclusive regarding the nature of the foot disorder. We considered the hypothesis of osteomyelitis of the navicular bone as the most likely, for which he completed six weeks of antibiotic therapy. There was a favorable clinical evolution, along with complete absence of osteoarticular or neurological sequelae. The relevance of this clinical case resides in the unusual presentation of invasive pneumococcal disease in this age group, as well as in the rare form of orthopedic involvement.